Contribution to the knowledge of Parajalla sanguineosignata (Spinola, 1852) (Heteroptera: Pentatomidae: Asopinae) in Patagonia - Carvajal, Mariom A.; Faundez, Eduardo; Rider, David A. (My University, 2017)
The nymphal instar V of Parajalla sanguineosignata (Spinola, 1852) is described. First formal records with specific locality data are given for Aysen and Magallanes Regions in Chile. San Gregorio becomes the southernmost locality known for this species.
Contribución al conocimiento de Parajalla sanguineosignata (Spinola, 1852) (Heteroptera: Pentatomidae: Asopinae) en Patagonia
Keywords: hemiptera; heteroptera; pentatomoidea; new record; immature stages; patagonia